Higher intake of microbiota-accessible carbohydrates and improved cardiometabolic risk factors: a meta-analysis and umbrella review of dietary management in patients with type 2 diabetes. Issue 6 (10th March 2021) - Xu, Bocheng; Fu, Jie; Qiao, Yanxiang; Cao, Jinping; Deehan, Edward C; Li, Zhi; Jin, Mingliang; Wang, Xinxia; Wang, Yizhen
ABSTRACT: Background: Microbiota-accessible carbohydrates (MACs) are critical substrates for intestinal microbes; the subsequent production of SCFAs may have some potential benefits for patients with type 2 diabetes mellitus (T2DM). Objectives: We conducted a meta-analysis of randomized controlled trials (RCTs) to assess the effects of higher compared with lower MAC intakes on cardiovascular risk factors in T2DM patients and performed an umbrella review of RCTs to evaluate the evidence quality concerning existing dietary T2DM interventions. Methods: Publications were identified by searching MEDLINE, EMBASE, and CINAHL. In the meta-analysis, random-effects models were used to calculate pooled estimates, and sensitivity analyses, meta-regression, subgroup analyses, and Egger's test were performed. For the umbrella review, we summarized pooled estimates, 95% CIs, heterogeneity, and publication bias. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) and modified NutriGrade were used to assess the quality of evidence in the meta-analysis and umbrella review, respectively. Results: Forty-five RCTs with 1995 participants were included in the meta-analysis. High MAC intake significantly reduced glycated hemoglobin (HbA1c) (weighted mean difference [WMD] –0.436% [–0.556, –0.315]), fasting glucose (WMD –0.835 mmol/L [–1.048, –0.622]), total cholesterol (WMD –0.293 mmol/L [–0.397, –0.190]), triglycerides (WMD –0.118 mmol/L [–0.308, –0.058]), BMI (WMD –0.476 [–0.641, –0.312]), and systolic blood pressure (WMD –3.066 mmHg [–5.653, –0.478]), with a moderate-to-high quality of evidence, compared with low intake. Region, dose, and MAC type were key variables. The umbrella review of all dietary interventions for cardiovascular risk factors in patients with T2DM included 26 meta-analyses with 158 pooled estimates. The evidence quality of MACs, dietary fiber, high-protein diet, ω-3 (n–3), viscous fiber, vitamin D, and vitamin E intake was moderate to high. Conclusions: When compared with lower intake, increased MAC intake improved glycemic control, blood lipid, body weight, and inflammatory markers for people with T2DM. This trial was registered at PROSPERO (https://www.crd.york.ac.uk/PROSPERO/#recordDetails ) as CRD42019120531.